Intervenciones de enfermería en la atención perioperatoria de pacientes con fijación intramedular por fractura de fémur: una revisión sistemática - Ashqui Inga, Darwin Elías (2026)
Nursing care during the perioperative period for patients with femur fractures treated with intramedullary fixation is essential to ensure effective, safe, and patient-centered recovery. The objective of this research was to standardize the main nursing interventions in the perioperative care of patients undergoing intramedullary fixation for femoral fractures. A non-experimental qualitative review was conducted, applying the PRISMA method for the selection of studies published between 2020 and 2025 on platforms such as PubMed and Dialnet. The results identified key strategies for pain management using nerve blocks and selective analgesia, supported by structured models such as ERAS and Orem's self-care model, along with early rehabilitation, nutritional, and psychological support. These interventions help reduce complications such as delirium, thrombosis, pressure ulcers, and infections, while improving patient functionality and quality of life. It is concluded that the nurse’s role must be comprehensive and personalized, incorporating clinical, educational, and emotional dimensions, and applying evidence-based care through updated clinical guidelines. This promotes a more efficient, humanized recovery process centered on each patient's individual needs.